Ecological restoration of the Los Angeles River provides natural and human benefits as part of a virtuous socioecological cycle - Katagi, Wendy; Butler, Nate; Keith, Anthony; Backlar, Shelly; Orr, Bruce (Frontiers in Ecology and Evolution, 2022)
Ecological restoration in the Los Angeles River watershed is proceeding on multiple fronts and with the support and engagement of diverse stakeholder groups. Pilot projects to restore habitat, reintroduce native species, and design science-based ecosystem enhancements have produced real benefits to nature and people in the watershed and demonstrated the potential for additional benefits. The pilot projects, which are in various stages of collaborative planning and implementation, have generated increased interest and financial support to further their implementation and maximize socioecological co-benefits. This self-reinforcing positive feedback is an example of a virtuous cycle established through a combination of long-term environmental planning, community-building, and watershed-scale scientific study to gain support of stakeholders and align ecological intervention (i.e., restoration) with the plans and policies of federal, state, and local government, resource managers, conservation groups, and grassroots advocacy groups. For example, the Los Angeles River Fish Passage and Habitat Structures project addresses a critical limiting factor for recovery of endangered steelhead trout while also enhancing urban biodiversity and providing recreational opportunities and other beneficial uses for the surrounding communities where up to 74% of the land is developed and access to nature is limited. Through these efforts, our team of planners, ecologists, and engineers is using place-based conservation to demonstrate solutions to problems that affect people and nature in many other urban landscapes and can not only provide socioecological benefits in disadvantaged communities but also generate awareness and motivate people to act in order to perpetuate the cycle of positive feedback.